2008
DOI: 10.1007/s00383-008-2194-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of the cystic form of meconium peritonitis: no issues for delayed postnatal surgery

Abstract: Prenatal ultrasound (US) diagnosis and postnatal outcome are reviewed in three babies with the complex form of meconium peritonitis (MP), the cystic type. Perinatal management is discussed. Large intra-abdominal cysts with signs of calcifications were detected during the second mid-trimester. Meconium ascites and polyhydramnios appeared between 32 and 35 weeks of gestation. Signs of anaemia were assessed on median cerebral artery peak systolic velocity. Sudden appearance of hydrops and anaemia required preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Patients with GCMP have a giant, thick-walled cyst containing meconium and fluid that occupies almost the entire peritoneal cavity. Previous studies have reported higher mortality in GCMP due to lung hypoplasia secondary to abdominal distension [12,13]. In our experience, GCMP accounted for the greatest number of patients and required the most contrivances during treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Patients with GCMP have a giant, thick-walled cyst containing meconium and fluid that occupies almost the entire peritoneal cavity. Previous studies have reported higher mortality in GCMP due to lung hypoplasia secondary to abdominal distension [12,13]. In our experience, GCMP accounted for the greatest number of patients and required the most contrivances during treatment.…”
Section: Discussionmentioning
confidence: 79%
“…The availability of high-resolution imaging equipments facilitated the perinatal diagnosis and management of most cases of MP and MPC [4, 5, 7]. The differential diagnosis of CMP includes haemangioma, teratoma, ovarian dermoid, hepatoblastoma, and metastatic neuroblastoma [8].…”
Section: Discussionmentioning
confidence: 99%
“…Once an antenatal diagnosis of complicated MP or MPC is reached, the mother should be referred to a tertiary care centre where close monitoring is possible and facilities for urgent perinatal intervention are available if needed [4, 9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rapid deterioration of fetal status can be possible in this type. In this regard meconium pseudocyst must be antenatally differentiated from other intra-abdominal cystic images such as urinary bladder distention, ovarian cyst, intestinal duplication, hematoma, teratoma and fetal infection5). FIF can be presented prenatally as an abdominal cystic mass with diffuse calcification or ossification by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%